Northern Adriatic environmental changes since 500 AD reconstructed at Aquileia (Italy). (1st July 2022) - Kaniewski, David; Marriner, Nick; Sarti, Giovanni; Bertoni, Duccio; Marchesini, Marco; Rossi, Veronica; Lena, Anna; Bivolaru, Alexandra; Pourkerman, Majid; Vacchi, Matteo; Cheddadi, Rachid; Otto, Thierry; et al.
Abstract: The fluvial harbour of Aquileia (Italy), one of the most important Roman trading centres in the Mediterranean, was abandoned after the city's destruction in 452 AD. The deserted harbour evolved into a swamp surrounded by a floodplain that has recorded the anthropogenic, environmental and climatic pressures that have occurred during the last 1500 years in the northern Adriatic. Focusing on the period since 500 AD, we here reconstruct the area's long-term ecosystem dynamics. We show that ecosystem dynamics mainly mirror the climate phases of the pre-industrial era. After the Roman era, anthropogenic activities (agriculture, pasture and fire activity) declined in scope and amplitude and are chronologically limited (from the late 7th to the early 13th centuries AD), acting as a background pressure on ecosystems. The main non-human impacts recorded by ecosystems correspond to the Late Antique Little Ice Age, defined by an average temperature anomaly of −2.04 ± 0.17 °C, exceeding the Pre-industrial Little Ice Age by −1.26 ± 0.16 °C in severity. The temperatures reconstructed for the Medieval Climate Anomaly are close to those recorded for the 20th century AD (average anomaly of 0.08 ± 0.15 °C) but they differ from the 21st century AD, according to the CRUTEM4 data. Aquileia shows that ancient harbours are key areas to understand how climate and human societies have shaped northern Adriatic environments since the post-Roman period. Highlights: Palaeoecological study of Aquileia, the ninth city of the Roman Empire. Insights into the ecosystem dynamics for the post-Roman period. Climate pressures shaped ecosystem dynamics. Anthropogenic activities acted as secondary pressures. Late Antique Little Ice Age was the coolest and driest episode recorded.